2020
DOI: 10.22296/2317-1529.rbeur.202024pt
|View full text |Cite
|
Sign up to set email alerts
|

Novo coronavírus (Sars-CoV-2): difusão espacial e outro patamar para a socialização dos investimentos no Brasil

Abstract: O artigo objetiva analisar os padrões de difusão espacial da Covid-19 no território brasileiro, considerando a organização dos sistemas de transportes, a rede urbana e as interações espaciais. Destacam-se também algumas estratégias e ações do Estado necessárias para combater a epidemia e influir no desenvolvimento econômico. Os sistemas de transportes e seus fluxos são vetores da difusão do novo coronavírus no território e esse processo permeia distintos momentos das interações espaciais no contexto das hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
3
0
1
Order By: Relevance
“…21 A study showed that the age group of people affected by the Influenza A/H1N1pdm09 virus in Brazil, in 2009, was predominant in children under 2 years old and adults aged between 20 and 29 years old. 6 On the other hand, data on the age group of people affected by COVID-19, in the literature investigated in this study, are in accordance with the main international statistics, which indicate the age above 60 years old. 22 On the incidence and mortality rates: the result of the disparity in the Brazilian regions may be related to the non-compliance with the isolation measures and the use of masks with the increase of cases in people of different ages.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…21 A study showed that the age group of people affected by the Influenza A/H1N1pdm09 virus in Brazil, in 2009, was predominant in children under 2 years old and adults aged between 20 and 29 years old. 6 On the other hand, data on the age group of people affected by COVID-19, in the literature investigated in this study, are in accordance with the main international statistics, which indicate the age above 60 years old. 22 On the incidence and mortality rates: the result of the disparity in the Brazilian regions may be related to the non-compliance with the isolation measures and the use of masks with the increase of cases in people of different ages.…”
Section: Discussionsupporting
confidence: 88%
“…The main Brazilian regions that had the highest incidence were the South and Southeast. 6 In December 2019, a series of cases of pneumonia caused by a β-coronavirus identified in Hubei province, Wuhan, China, were reported. 9 On January 12, 2020, the disease was named COVID-19 and on March 11 this year a pandemic state was declared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial analysis of the coronavirus spread can provide an important tool for the management of public health, showing the routes of disease dispersion and the fragility of the municipalities concerning their sociodemographic characteristics (GUIMARÃES et al, 2020). In the case of COVID-19, Silveira et al (2020) have highlighted that in countries like Brazil, its dissemination occurred mainly through commercial passenger aviation, following primarily the configuration and logic of the urban hierarchy networks, transport and the population arrangement of cities.…”
Section: Risk and Social Vulnerabilities In The Brazilian Context Of mentioning
confidence: 99%
“…De mesmo modo, Silveira et al (2020) e Barros (2021) constataram que a pandemia da Covid-19 acentuou os problemas decorrentes do processo de globalização totalitária ou globalitária, conforme discussões anteriores de Milton Santos (2000). Seus reflexos nos serviços públicos e nos sistemas privados de saúde, em vários países ultraneoliberais , e a dependência comercial dos produtos chineses para garantir as medidas iniciais de enfrentamento de difusão do vírus ) explicam a fragilidade de ideias como governança global com controle político e econômico-territorial, gestão estatal dirigida aos interesses do mercado e da reprodução do capital, capacidade de resposta do capitalismo neoliberal a crises e catástrofes sanitárias e a dependência unilateral de centros produtores de insumos e suprimentos globais.…”
unclassified